Lenalidomide, bendamustine and prednisolone exhibits a favourable safety and efficacy profile in relapsed or refractory multiple myeloma: final results of a phase 1 clinical trial OSHO – #077. (21st May 2013) - Pönisch, Wolfram; Heyn, Simone; Beck, Juliane; Wagner, Ina; Mohren, Martin; Hoffmann, Franz A.; Lange, Thoralf; Schmalfeld, Marion; Zehrfeld, Thomas; Schwarzer, Andreas; Winkelmann, Cornelia; Edelmann, Thomas; et al.
Summary This phase 1 dose finding study tested a combination of lenalidomide, bendamustine and prednisolone (RBP) in 21 patients in five cohorts with advanced multiple relasped/refractory myeloma (MM) to determine the maximum tolerable dose (MTD) of the combination. The first cohort received a starting dose of lenalidomide 10 mg/d, days 1–21, bendamustine 60 mg/m2/d, days 1–2, and prednisolone 100 mg/d, days 1–4. Dose escalation was done in cohorts of three to six patients with lenalidomide dose increasing to 15, 20 and 25 mg, and after reaching 25 mg/d, bendamustine was increased to 75 mg/m2. A total of 21 patients were enrolled and all completed at least two cycles. Two patients developed dose‐limiting haemotoxicity: one patient on lenalidomide 25 mg/d and bendamustine 60 mg/m2 and another patient at the highest dose level (lenalidomide 25 mg/d and bendamustine 75 mg/m2). The MTD was not reached. Sixteen patients (76%) responded after at least two cycles of RBP with one stringent complete response (CR), one near CR, five very good partial response and nine partial response. After a median observation time of 16 months, progression‐free survival at 18 months was 48% and overall survival was 64%. In conclusion, RBP with lenalidomide 25 mg/d, days 1–21 and bendamustine 75 mg/m2 days 1–2 is well tolerated in patients with relapsed/refractory MM.